Somatostatin as Inflow Modulator in Liver-transplant Recipients With Severe Portal Hypertension: A Randomized Trial. Issue 6 (June 2019) - Troisi, Roberto Ivan; Vanlander, Aude; Giglio, Mariano Cesare; Van Limmen, Jurgen; Scudeller, Luigia; Heyse, Bjorn; De Baerdemaeker, Luc; Croo, Alexander; Voet, Dirk; Praet, Marleen; Hoorens, Anne; Antoniali, Giulia; et al.
Abstract : Objective: To investigate the safety and efficacy of somatostatin as liver inflow modulator in patients with end-stage liver disease (ESLD) and clinically significant portal hypertension (CSPH) undergoing liver transplantation (LT) (ClinicalTrials.gov number, 01290172). Background: In LT, portal hyperperfusion can severely impair graft function and survival, mainly in cases of partial LT. Methods: Thirty-three patients undergoing LT for ESLD and CSPH were randomized double-blindly to receive somatostatin or placebo (2:1). The study drug was administered intraoperatively as 5-mL bolus (somatostatin: 500 μg), followed by a 2.5 mL/h infusion (somatostatin: 250 μg/h) for 5 days. Hepatic and systemic hemodynamics were measured, along with liver function tests and clinical outcomes. The ischemia-reperfusion injury (IRI) was analyzed through histological and protein expression analysis. Results: Twenty-nine patients (18 receiving somatostatin, 11 placebo) were included in the final analysis. Ten patients responded to somatostatin bolus, with a significant decrease in hepatic venous portal gradient (HVPG) and portal flow of −28.3% and −29.1%, respectively. At graft reperfusion, HVPG was lower in patients receiving somatostatin (−81.7% vs −58.8%; P = 0.0084), whereas no difference was observed in the portal flow ( P = 0.4185). Somatostatin infusion counteracted the decrease in arterial flow (−10% vs −45%; P = 0.0431). There was no difference between the groups in the severity of IRI, incidence of adverse events, long-term complications, graft, and patient survival. Conclusions: Somatostatin infusion during LT in patients with CSPH is safe, reduces the HVPG, and preserves the arterial inflow to the graft. This study establishes the efficacy of somatostatin as a liver inflow modulator. Abstract : Supplemental Digital Content is available in the text